Blockade of the Mineralocorticoid Receptor in Healthy Men: Effects on Experimentally Induced Panic Symptoms, Stress Hormones, and Cognition - Otte, Christian; Moritz, Steffen; Yassouridis, Alexander; Koop, Maike; Madrischewski, Ana Maria; Wiedemann, Klaus; Kellner, Michael (Neuropsychopharmacology (New York, N.Y.), 2007)
Animal studies have shown that blockade of central mineralocorticoid receptors (MR) has anxiolytic effects and impairs several aspects of cognitive function. No study to date assessed the effects of MR blockade on anxiety and cognitive function in humans. In the present study, 16 healthy young men were treated either with placebo or with 300 mg spironolactone, a MR-antagonist, at 1100, 1330, and 1630 hours in a balanced cross-over design with the two study conditions being 1 week apart. At 1500 hours, the panic symptoms provoking compound cholecystokinin-tetrapeptide (CCK-4) was administered i.v. on both occasions and panic symptoms were assessed. We measured plasma ACTH and cortisol between 1300 and 1900 hours and assessed cognitive function between 1800 and 1900 hours. CCK-4 elicited panic symptoms and increased ACTH and cortisol secretion in both conditions. Intensity of panic symptoms after CCK-4 was not different between spironolactone and placebo. Spironolactone significantly impaired selective attention and delayed recall of visuospatial memory, and diminished set shifting/mental flexibility on a trend level. Pretreatment with spironolactone led to higher baseline cortisol levels compared to placebo whereas no differences in stimulated cortisol, baseline ACTH, and stimulated ACTH emerged. Blockade of MR with spironolactone increases baseline cortisol secretion and impairs cognitive function but has no effect on experimentally induced panic symptoms in humans, for the study design and dosage of spironolactone used. The domains of cognitive function that are impaired after blockade of MR in men, that is, selective attention, visuospatial memory, and mental flexibility/set shifting appear to be remarkably similar to those described in animal studies.